2016
DOI: 10.1038/ncomms11914
|View full text |Cite
|
Sign up to set email alerts
|

KRT14 marks a subpopulation of bladder basal cells with pivotal role in regeneration and tumorigenesis

Abstract: The urothelium is a specialized epithelium that lines the urinary tract. It consists of three different cell types, namely, basal, intermediate and superficial cells arranged in relatively distinct cell layers. Normally, quiescent, it regenerates fast upon injury, but the regeneration process is not fully understood. Although several reports have indicated the existence of progenitors, their identity and exact topology, as well as their role in key processes such as tissue regeneration and carcinogenesis have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(154 citation statements)
references
References 22 publications
7
147
0
Order By: Relevance
“…Our observation that the PRC2-mediated H3K27me3 epigenetic mark is highly enriched and variable in the urothelium suggest the possibility that different levels of H3K27me3 may reflect diverse basal, intermediate and superficial cell types. Papafotiou et al (2016) show that Krt14 expression marks a subpopulation of murine bladder basal cells with essential roles in regeneration and tumorigenesis. Expression of KRT14 is also linked to human bladder cancer development (Cancer Genome Atlas Research Network, 2014;Sjodahl et al, 2012;Volkmer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observation that the PRC2-mediated H3K27me3 epigenetic mark is highly enriched and variable in the urothelium suggest the possibility that different levels of H3K27me3 may reflect diverse basal, intermediate and superficial cell types. Papafotiou et al (2016) show that Krt14 expression marks a subpopulation of murine bladder basal cells with essential roles in regeneration and tumorigenesis. Expression of KRT14 is also linked to human bladder cancer development (Cancer Genome Atlas Research Network, 2014;Sjodahl et al, 2012;Volkmer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mature bladder urothelium has a very low turnover rate. However, injuries such as urinary tract infection (UTI) or cyclophosphamide (CPP) treatment trigger a rapid proliferative response of the basal and intermediate cells to regenerate superficial cells (Colopy et al, 2014;Gandhi et al, 2013;Kunze et al, 1980;Mysorekar et al, 2009;Papafotiou et al, 2016;Shin et al, 2011). While the molecular mechanisms underlying the urothelial quiescent state and regenerative capacity remain largely unknown, these studies begin to uncover the cellular basis of urothelial regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the lineage restriction of myoepithelial cells, and the finding that cells expressing Krt5 and Krt14 behave as progenitors in many other epithelial organs (Blanpain and Fuchs, 2009;Papafotiou et al, 2016;Rock et al, 2009), we next determined whether basal cells marked by KRT5 and KRT14 could contribute to all epithelial lineages in the developing and adult lacrimal gland. After confirming that KRT5 (and KRT14) mark a distinct ACTA2-negative basal epithelial population around ducts (Fig.…”
Section: Progenitor Potential Of the Basal Cell Layer In The Developimentioning
confidence: 99%
“…The uroplakin-marked cells formed noninvasive papillary lesions, whereas the cytokeratin 5-marked basal cells contributed to carcinoma in situ and muscle-invasive lesions [6]. Two other studies used the sonic hedgehog promoter [9] and cytokeratin 14 promoter [10] to mark urothelial basal cells, and showed that muscle-invasive bladder cancer originated from basal cells. It should be noted that all these lineage tracing studies used the N-butyl-N-(4-hydroxybutyl)nitrosamine-based chemical carcinogenesis model, and none addressed the subtypes of muscle-invasive bladder cancer.…”
mentioning
confidence: 96%